Supply Chain Quality Accounting Information Systems with Business Strategy Effective in Bumn Bandung Indonesia - Nur Zeina Maya Sari; Azhar Susanto; Nunuy Nur Afiah; Memed Sueb; Harry Suharman (International Journal of Supply Chain Management, 2019)
Purpose study aims to determine Supply Chain Quality of Accounting Information Systems, with Business Strategy at BUMN in Bandung Indonesia. The function accounting information system is to provide information important to reduce uncertainty, support decisions, and encourage better, scheduling, and job control. An important business strategy in the implementation of an effective information system. This study uses descriptive methods and types of research that are verification. The type of data which is the primary using primary data uses an interval scale for measurement. Validity and reliability tests were carried out on the collected questionnaires, then ordinal-scale data in interval then using MSI (interval measurement). Data analysis was performed using SPSS. The Supply Chain Quality Accounting Information System at BUMN is not good, there is no fast and Quality of accounting information systems with business strategies effective. The accounting information system is not yet fully qualified.